Synthesis and Characterization of Novel Water Soluble Starch Tartarate Nanoparticles - Pang, Suh Cem; Chin, Suk Fun; Lim, Lih Shan (Hindawi Publishing Corporation, 2012)
Starch tartarate nanoparticles were prepared by esterification reaction between native sago starch (Metroxylon sagu) and tartaric acid using dimethyl sulphoxide (DMSO) as a solvent and 2-dimethylamino pyridine (DMAP) as a catalyst at 100◦C. The substitution of tartaric acid onto native sago starch was confirmed by the FTIR spectra which showed the presence of carbonyl group absorption band of tartarate ester. The solubility of the as-synthesized starch tartarate nanoparticles was observed to increase linearly with increase in the degrees of substitution. Under optimized synthesis conditions, starch tartarate nanoparticles of mean particle sizes which ranged from 200 nm to 300 nm were produced.